Residential-employment mixed use and jobs-housing balance: A case study of Shenzhen, China. (August 2022) - Zhou, Xingang; Yeh, Anthony G.O.; Yue, Yang; Li, Weifeng
Abstract: Residential-employment mixed use has often been proposed to promote jobs–housing balance and to increase employment self-containment of residents, thereby reducing commuting distance and motorized travel. However, the relationship between residential-employment mixed use and work trips has few consensuses. Whether residential-employment mixed use is correlated with employment self-containment of residents remains to be explored. In this study, the relationships between residential-employment mixed use and employment self-containment of residents are examined in the industrial and commercial areas in Shenzhen, China. The relationships between commercial–residential and industrial–residential mixes and employment self-containment of residents are examined using mobile phone data. Results indicate that residential-employment mixed use is positively correlated with employment self-containment of residents in industrial–residential mix areas in the suburbs, but is not correlated in commercial–residential mix areas in the central city. Residential-employment mixed use alone does not achieve high employment self-containment of residents, which also depends on other factors such as its economic sector, location, and housing prices. Highlights: Residential-employment mixed use is not a sufficient condition in commercial–residential mix areas. Other factors can also influence the correlation between residential-employment mixed use and jobs-housing balance. This study will enhance our understanding of residential-employment mixed use and jobs-housing balance.